Formation of the Rational Socio-Economic Worldview Based on the Laws of Nature and Society - N. Semin, Alexander; A. Potekhin, Nikolai; N. Potekhin, Viktor (International Journal of Criminology and Sociology, 2022)
The study is aimed at the improvement of social and economic relations based on modern directions of the formation of a rational socio-economic worldview, eliminating the sociological contradictions of modern society. The use of a system-holistic interdisciplinary methodology determines the need to review the development tools of the problem of creating a rational worldview in society. The basis of the research methodology has become the conceptual matrix of the formation of a rational worldview according to community levels, taking into account the basic socio-economic law of human development in any system. The article presents the results of a study designed as a clarification of the concept of “rational worldview”, creating a list of the benefits of forming a rational socio-economic worldview based on the laws of nature and society, and determining the directions of formation of a rational worldview in the context of the topic under study. The results of the study can be used in the system of state management of economic processes. Novelty/Originality of this study: (1) actualized, based on the systematization of scientific views, the theoretical provisions of the formation of a rational socio-economic worldview and determined the modern directions of its development; (2) the analysis of modern practices of the life of modern society is carried out and the logical and ideological contradictions in the field of behavioral economics are highlighted; (3) the conceptual apparatus of the category “rational worldview” has been clarified in the context of the contradictions in the functioning of socio-economic systems; (4) a conceptual matrix for the formation of a rational worldview has been developed; (5) the advantages of the formation of a rational worldview among the subjects of the development of society are formulated, based on social criteria analysis.